Pengaruh Non-Performing Financing, Dana Pihak Ketiga, Dan Likuiditas Terhadap Profitabilitas Bank Syariah Di Indonesia - Zakaria, Muhammad Rizki; Yoga, Andriawan; Dwiputri, Inayati Nuraini (Jurnal Ekonomika dan Bisnis Islam, 2025)
Islamic banks function as financial intermediaries that mobilize public funds through Sharia-compliant contracts and channel them into financing activities. The primary source of financing comes from Third-Party Funds, while liquidity risks and financing strategies play a critical role in determining financial performance. This study aims to see the effect of Non-Performing Financing, Third Party Funds, and liquidity on the profitability of Islamic banks in Indonesia. Non-Performing Financing is represented by Non-Performing Financing ratio and liquidity is represented by Short-Term Mistmach ratio. Profitability is represented by the Return on Asset ratio. The method employed in this study is a quantitative research method. The data utilized consist of secondary data from Islamic Banking Statistics covering the period from the first quarter of 2015 to the fourth quarter of 2023. The results of this study show that DPK has a significant effect on the profitability of Islamic banks. While NPF and liquidity have no significant effect on the profitability of Islamic banks. The mobilization of Third-Party Funds constitutes a key strategy for enhancing the profitability of Islamic banks in Indonesia, while prudent management of non-performing financing (NPF) and liquidity is essential to sustain stability and maintain public confidence in the Islamic banking sector.